1978
DOI: 10.1111/j.1399-3011.1978.tb02888.x
|View full text |Cite
|
Sign up to set email alerts
|

Syntheses of Monocyclic and Bicyclic Peptides of Tryptathionine and Glycine

Abstract: L‐3a‐Hydroxy‐1.2.3.3a.8.8a‐hexahydropyrrolo[2,3‐b‐]‐indole‐2‐carboxylic acid (Hpi)*, obtained from L‐tryptophan by oxidation with peroxyacetic acid (Savige, 1975), after introduction of the Boc‐residue at N‐1, is coupled with various glycine peptides of S‐trityl‐L‐cysteine to give the Hpi‐peptides 6(a‐f). By treatment with absolute trifluoroacetic acid these peptides are converted by an intramolecular thiolysis to the monocyclic thioethers 7(a‐f). Two of them, 7e and 7f, can be subjected to a second cyclizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

1979
1979
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…A review of peptide cyclization and cyclopeptides has only recently appeared [731]. Many examples for the synthesis of cyclic and bicyclic peptides can be found in the literature [732740]. Kubik et al published a comprehensive review about cyclopeptides as macrocyclic hosts [741].…”
Section: Reviewmentioning
confidence: 99%
“…A review of peptide cyclization and cyclopeptides has only recently appeared [731]. Many examples for the synthesis of cyclic and bicyclic peptides can be found in the literature [732740]. Kubik et al published a comprehensive review about cyclopeptides as macrocyclic hosts [741].…”
Section: Reviewmentioning
confidence: 99%
“…In fact, Zanotti et al. reported on an attempted Savige–Fontana reaction with an N‐acetylated Hpi; no tryptathionine formation was observed, and hence, it was concluded that the N‐acylated Hpi was resistant to acid catalysed ring opening and tryptathionylation 25. 26 In contrast to that finding, here we describe the first synthesis of an intraannular tryptathionine linkage derived from an N‐acylated Hpi moiety incorporated internally within a peptide chain (see below).…”
Section: Introductionmentioning
confidence: 68%
“…To date, several strategies have been used to form synthetic bicyclic peptides. The first strategy was reported to generate a bicyclic tryptathionine heptapeptide in 1978 by Zanotti et al [16]. In this method, the first step of cyclization involved formation of a thioether bond between a cysteine residue and a derivative of Ltryptophan, which was generated by oxidation with peroxyacetic acid.…”
Section: Chemical Methods For Cyclization Of Peptidesmentioning
confidence: 99%